EVALUATION OF FUNCTIONING AND STATUS OF IMPLEMENTATION OF HEMOVIGILANCE PROGRAM OF INDIA IN THE BLOOD BANKS OF SOUTHERN KERALA - Pk, Sreekumar; Tm, Pramod Kumar; G, Partha Sarathi; Gupta, Debasish; Prakash, Pallavi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to evaluate the functioning and status of implementation of hemovigilance program of India (HvPI) in the blood banks of southern Kerala. Methods: It was a survey approach to analyze the facilities, working nature, and status of implementation of hemovigilance program by the blood banks located in the three districts of southern Kerala. Both goevrnment and private sector blood banks were subjected to the survey. Standard pro forma was used to collect the data. Collected data were analyzed by percentages and ratios. Results: A total of 40 blood banks were covered in the study. All the blood banks were licensed for handling whole blood. 23 blood banks were licensed for handling blood components. 6 blood banks process 100% blood into components. Majority of blood banks have excellent demand for components. Packed red cells, platelet concentrate, and fresh frozen plasma were the significant components among the prepared components. Majority of the blood banks under the survey had hospital transfusion committee (HTC). 25 blood banks replied as the HvPI is an excellent/good system. However, only 11 blood banks were enrolled in the HvPI. Training programs for the resident doctors and nurses regarding with adverse transfusion reaction and their reporting were not conducted by 17 blood banks. Conclusion: Except very few blood banks, all are need more awareness and training programs. Attention should be given in the area such as underreporting, poor implementation of hemovigilance, only serious reactions reporting, and avoiding minor reactions. Core factor is proper functioning of HTC and awareness programs about hemovigilance system.